Optimization of Early Detection by Unit 1 Sat Intelkam to Prevent Theft Crimes in the Legal Area of Boyolali Police Resort - Rauf, Satya Ryan Pratama Kusuma Putra (Advances in Police Science Research Journal, 2024)
The rampant theft crimes in Boyolali District have become a problem and caused concern for the community in Boyolali District. The Indonesian National Police (Polri) must take preventive measures against such criminal acts through prevention activities carried out by Unit 1 Sat Intelkam of Boyolali Police Resort. This study aims to identify the performance of Unit 1 Sat Intelkam of Boyolali Police Resort in preventing theft crimes in the legal area of Boyolali Police Resort. This study used a qualitative approach and field research method. Data collection was carried out by conducting interviews, observations, and document studies. The data analysis technique used was data collection, data reduction, data presentation, and conclusion drawing. This study uses conceptual literature including the concepts of optimization, early detection, Intelkam, theft crimes, public order and security, management theory, motivation theory, and SWOT theory. The factual condition in this study is the suboptimal performance of Unit 1 Sat Intelkam of Boyolali Police Resort. In carrying out their duties, their performance is influenced by internal and external factors. Internal factors include the lack of quantity and quality of personnel, the application in development, and the lack of motivation. Meanwhile, external factors include coordination and cooperation with related functions as well as the community to support the performance of Unit 1 Sat Intelkam.